Sources of Financing and Firm Growth: Evidence from Ethiopia. (9th April 2019) - Regasa, Dereje; Fielding, David; Roberts, Helen
Abstract: Using Ethiopian firm-level data, we model the effect of different types of financing on firm growth. The form of financing is potentially endogenous to firm growth, and one contribution of this paper is to introduce a new instrumental variable which captures local variation in financial depth. Unlike previous studies of firms in low-income countries, we find evidence for a negative relationship between the use of external finance and the firm growth, which suggests that there are substantial cross-country differences in the finance-growth nexus. We discuss possible explanations for this phenomenon and its implications for development policy.